The role of management in training programmes on learning motivation from the Islamic perspective - Nur Izzaty Mohamad; Suhaila Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The training programme is a critical function in human resource management that can help enhance the competitiveness and performance of organisations in the global competition era. From an Islamic and empirical perspective, most early studies on organisational training have found that the role of management in training programmes can enhance learning motivation. Although this nature has been extensively studied, the role of management in training programmes is not thoroughly discussed in the literature on Islamic and Western training management studies. This study assessed the nature of the role of management in training programmes (management support and training content) and learning motivation based on structured interviews to collect data from public sector employees in Malaysia. The study’s findings explain that the management’s ability to fulfil its role consistently can stimulate employee learning motivation. The findings can serve as a guide for practitioners to understand the complexity of the role of management in designing training programmes and in formulating a strategic action plan. This plan aims to enhance leadership training skills to achieve and maintain organisational goals and strategies in the era of globalisation and a knowledge-based economy.